Kontribusi Asosiasi Peternakan Ayam Broiler Pada Anggotanya - Roisu Eny Mudawaroch; Sunardi Sunardi (Jurnal Riset Agribisnis dan Peternakan, 2020)
The existence of the community allows an increase in the business of laying hens. The existence of the “Berkah telur Makmur’ association motivates these breeders to emerge because the breeders feel that the laying hen business can support their social relationships and can be developed as a family business. The purpose of this study was to determine the benefits of joining a laying hen association in the Purworejo area. This research was conducted at the association of laying hens in "Berkah Egg Makmur" which includes Purworejo Regency, Magelang Regency, Kebumen Regency, and Wonosobo Regency. Samples were taken randomly from 25 farmer groups. This research was designed as a descriptive study. Data analysis used descriptive statistics in the form of frequency distribution and percentage. The results showed that farmers received 88% of the benefits of information, 8% of market guarantees and 4% of price avoidance. The facility of the laying hen breeders' association is counseling. Counseling was attended by 52% members, while 40% never attended and followed counseling from associations and counseling from outside as much as 8%. 44% of the members of the association who attended the counseling (1-5 times), while 12% were more than 5 times. Information obtained apart from association comes from 20% of the internet, 8% of print media and 70% of fellow breeders. The association's response to 68% was swift. The conclusion of this study is that there is an association of laying hens that provides benefits for laying hen farmers, contributes and provides benefits. There is a need for various outreach to make it more attractive to its members and to increase the association's response to its members.